Business English and communication - Clark, Lyn R.; Zimmer, Kenneth; Tinervia, Joseph (Toronto: McGraw-Hill Ryerson, 1996)
Emphasizes the English and communication skills that are necessary in the business world, including speaking, listening, reading, and writing.
Includes index.
Keywords: English language-Business English; Business writing